Gender Analysis in Athletes' Representation of TV program broadcast just before the 2016 Rio Olympics - YAMAMOTO, Natsuki (Journal of Sport and Gender Studies, 2024)
There is a great deal of research on gender representation in sports coverage. In particular, the Summer Olympics and female athletes are the main research subjects, and there is a certain amount of accumulation of research in Japan. There have been reports of lookism and privacy for female athletes, and are also reports that trivialize the achievements of female athletes. Although such studies have been accumulated, mainly with TV news as a central example, it is difficult to say that consideration of the TV programs of other genres is progressing.The purpose of the article is to examine whether gender differences really exist and to clarify the gender consciousness latent in television itself. Therefore, we had focused on two pre-Olympics TV programs that were broadcast just before the Rio Olympics (August 5, 2016). Qualitative content analysis was conducted on the VTR message and the comments of the performers in these TV programs. We checked the ratio of men and women appearing on TV screens and examined whether there was a gender difference in. As a result of this study, some expressions of masculinity and femininity, which had been pointed out in the past were introduced, but at the same time, many gender differences were discovered. In particular, expressions that trivialize the achievements of female athletes are clear. This study revealed the reality of gender consciousness hidden in television itself. It is necessary to continue to stare at and point out that gender expression differences have always arisen in television throughout the global event of the Olympic Games.